Neutralization of RANTES and Eotaxin Prevents the Loss of Dopaminergic Neurons in a Mouse Model of Parkinson Disease - Chandra, Goutam (J Biol Chem, 2016)
Parkinson disease (PD) is second only to Alzheimer disease as the most common human neurodegenerative disorder. Despite intense investigation, no interdictive therapy is available for PD. Recent studies indicate that both innate and adaptive immune processes are active in PD. Accordingly, we found a rapid increase in RANTES (regulated on activation normal T cell expressed and secreted) and eotaxin, chemokines that are involved in T cell trafficking, in vivo in the substantia nigra pars compacta and the serum of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-intoxicated mice. RANTES and eotaxin were also up-regulated in the substantia nigra pars compacta of post-mortem PD brains as compared with age-matched controls. Therefore, we investigated whether neutralization of RANTES and eotaxin could protect against nigrostriatal degeneration in MPTP-intoxicated mice. Interestingly, after peripheral administration, functional blocking antibodies against RANTES and eotaxin reduced the infiltration of CD4(+) and CD8(+) T cells into the nigra, attenuated nigral expression of proinflammatory molecules, and suppressed nigral activation of glial cells. These findings paralleled dopaminergic neuronal protection, normalized striatal neurotransmitters, and improved motor functions in MPTP-intoxicated mice. Therefore, we conclude that attenuation of the chemokine-dependent adaptive immune response may be of therapeutic benefit for PD patients.